The use of birthing balls during labour: a systematic literature review - Cristiana Teixeira; Maria Otília Zangão (Millenium)
Introduction: Birthing balls have emerged as a valuable alternative in childbirth care, promoting not only pain relief but also a more positive and empowering experience while minimizing the need for invasive medical interventions. This holistic, woman-centered approach can positively transform the experience, contributing to healthier and more satisfying maternal and neonatal outcomes.